Response to comments on "Ionic transport in (Nano)composites for fuel cells, Int. J. Hydrogen Energy 41 (2016) 7666–7675": Mishandling of literature data on ionic conductivity enhancement in oxide+salt composites. (21st September 2017) - Rondão, A.I.B.; Martins, N.C.T.; Patrício, S.G.; Marques, F.M.B.
Abstract: A recent commentary suggesting mishandled literature data in the analysis of the performance of composites including salts (alkaline carbonates) and oxides (pure ceria) is shown here as invalid. Even inadequately invoked data for the salt conductivity is shown to remain below the required performance. This conclusion is inevitable when due attention is paid to the salt volume fraction (50 vol%) and electrical pathway (tortuosity, ≥2) within the composite, both decreasing the effective electrical conductivity with respect to the fully dense salt. Furthermore, newly invoked data is inadequate for not being representative of the properties of the salt under analysis, including mismatching chemical composition and electrical performance. Other issues transgressing usual standards in scientific communications are also shortly addressed.